The Role of Family Counseling in Addressing the Problem of Divorce and Protecting the Family - علي, افتخار مزهر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The current research is determined to identify the measurement of (the role of family counseling in treating the problem of divorce and protecting the family). In order to achieve the research objectives، the researcher followed the descriptive approach in describing the phenomenon and using the family counseling method in solving the problem through the use of its techniques، which are affirmation training، symbolic economy، solving problems in the judiciary، and reducing divorce The researcher adopted the case study method using in-depth interviews. The research community was determined as divorced women between the ages of (20-40 years). (10) cases of divorced women were deliberately chosen to answer the survey questionnaire. After that، the questionnaire was distributed to (50) divorced women. The study reached several results، including: the emergence of the Internet and social media، and the lack of compatibility and harmony between spouses and Emotional divorce، childlessness، and the economic situation were among the most important reasons leading to divorce. It was also shown that family counseling plays an effective role in treating and resolving the problem of divorce by dealing with mood swings and emotions، improving psychological health، creating balanced relationships with others and their children، eliminating feelings of anxiety، restoring balance and harmony to their lives، and integrating them into society.